Neuropathic Pain in Females with Fibromyalgia Syndrome: The Role of Obesity - Meltem Yener Mankır; Özge Ardıçoğlu; Berat Meryem Alkan; Fatma Fidan (Galenos Yayinevi, 2023)
Objective:This study aimed to assess the impact of obesity on neuropathic pain, fibromyalgia symptoms, and quality of life in female patients diagnosed with fibromyalgia syndrome.Materials and Methods:This study enrolled 40 normal-weight and 40 obese female patients who were diagnosed with fibromyalgia syndrome. The patients enrolled in this study satisfied all of the American Collage of Rheumatology (ACR) 1990 and 2010 classification criteria. For fibromyalgia syndrome. The Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scale and douleur neuropathique 4 questions (DN4) scale was used to assess the extent of neuropathic pain experienced by the patients enrolled in this study. The assesment of patient health status was conducted using the Fibromyalgia Impact Questionnaire (FIQ) scale.Results:Based on the results obtained from the LANSS scale, neuropathic pain was identified in 56.3% patients, while according to the DN4 scale, it was present in 78% of the patients. The analysis of data from the LANSS scale revealed that 42.5% of the patients in the normal weight group and 70% of the patients in the obese group had neuropathic pain. Furthermore, the prevalence of neuropathic pain was significantly higher among the patients in the obese group. The comparison of quality of life scores using the FIQ scale between the two groups did not reveal any statistically significant variation.Conclusion:Neuropathic pain is high in female patients with fibromyalgia syndrome (FMS). Neuropathic pain was significantly higher in the obese group. Therefore, obese women with FMS would benefit from an increased focus on managing their neuropathic pain.